Effect of external loading on liquid metal embrittlement severity during resistance spot welding. (August 2022) - DiGiovanni, C.; Shojaee, M.; Biro, E.; Zhou, N.Y.
Abstract: Advanced high strength steels (AHSS) used in automotive structural components are protected using zinc coatings. However, the steel/zinc system creates the potential for liquid metal embrittlement (LME) during resistance spot welding (RSW). Manufacturing conditions, such as mechanical restraint, were simulated by external loading on the sample during welding. The results showed increased LME severity in all cases, but the material response to external loading was different depending on the material's inherent susceptibility to LME. Therefore, the manufacturing conditions are more critical for certain AHSS grades. This work provides guidelines on process design for LME mitigation and awareness during manufacturing.